(untitled) (Annals of Medical Research, 2021)
Aim: Neutrophil-to-eosinophil ratio (NER) shows inflammation, which can play a role in the development of some epilepsies and ictogenesis. The current study aimed to investigate the NER and the variations in neutrophil and eosinophil levels in epilepsy patients with generalized tonic-clonic seizures.Material and Methods: Epilepsy patients with generalized tonic-clonic seizures were retrospectively evaluated in the present study. Laboratory parameters of the patients in the acute (within 6 hours after the seizure) and subacute (on day 5 after the seizure) phases were compared.Results: 60 patients (30 males and 30 females) who had generalized tonic-clonic epileptic seizures were included in the study. The median neutrophil count and NER were significantly higher in the acute phase than in the subacute phase (p0.001). The median C-reactive protein and eosinophil values and the mean lymphocyte count were significantly lower in the acute phase than in the subacute phase (p0.001). Conclusions: NER can be used as a new potential biomarker of systemic inflammation that triggers seizures in generalized tonic-clonic epileptic seizures. Further studies are needed for the role of NER in epilepsy and epileptic seizures.